2015
DOI: 10.2147/dmso.s79221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eprosartan-based antihypertensive therapy on coronary heart disease risk assessed by Framingham methodology in Canadian patients with diabetes: results of the POWER survey

Abstract: ObjectiveAs part of the Physicians’ Observational Work on Patient Education According to their Vascular Risk (POWER) survey, we used Framingham methodology to examine the effect of an eprosartan-based regimen on total coronary heart disease (CHD) risk in diabetic patients recruited in Canada.MethodsPatients with new or uncontrolled hypertension (sitting systolic blood pressure [SBP] >140 mmHg with diastolic blood pressure <110 mmHg) were identified at 335 Canadian primary care practices. Initial treatment cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, a meta-analysis of seven randomized trials (TRACE, SOLVD, ValHeFT, CHARM, etc.) demonstrated that treatment with ACE inhibitors and angiotensin-receptor blockers reduced the risk of atrial fibrillation (AF) and sudden cardiac death due to left ventricular hypertrophy regression, provided protection against atrial enlargement and supraventricular arrhythmias, as well as affected endothelial function, risk biomarkers and vascular remodelling [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a meta-analysis of seven randomized trials (TRACE, SOLVD, ValHeFT, CHARM, etc.) demonstrated that treatment with ACE inhibitors and angiotensin-receptor blockers reduced the risk of atrial fibrillation (AF) and sudden cardiac death due to left ventricular hypertrophy regression, provided protection against atrial enlargement and supraventricular arrhythmias, as well as affected endothelial function, risk biomarkers and vascular remodelling [15,16,17].…”
Section: Introductionmentioning
confidence: 99%